The Analysis of Hegemony in Terra Nullius Novel by Claire G. Coleman - Yoga Pratama (Universitas Sebelas Maret, 2024)
A B S T R A C TThis research aims to analyze hegemony in Terra Nullius a novel by Claire. G. Coleman uses Antonio Gramsci’s theory in literary studies and sociology. The research focuses on discussing the concept of hegemony that occurs in the main character. The theory in literary studies is used to analyze the novel, using an intrinsic approach including characterization, plot, and setting which is elaborated through an extrinsic approach related to hegemony. This research used a qualitative method with data collection techniques including literature study, observation, and note-taking. The main data used are novels and several books and journals to support the research. The results of the research in the novel Terra Nullius are the concept of hegemony and the state involving civil society, namely the Natives called Aboriginals, with Settlers communities, Europeans. In the hegemony that occurs, the practice of supremacy has been found, namely a group that manifests itself in leadership that dominates the opposition to destroy or subdue the Aboriginals with weapons. All done to win power over the nobody land called Australia. Consequently, it became an Integral state, a hegemony shielded by the systems of violence.